2016
DOI: 10.1136/openhrt-2016-000472
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells and acute coronary syndromes: relationship between serum tryptase, clinical outcome and severity of coronary artery disease

Abstract: ObjectiveTo assess the relationship between serum tryptase and the occurrence of major cardiovascular and cerebrovascular events (MACCE) at 2-year follow-up in patients admitted with acute coronary syndrome (ACS). To compare serum tryptase to other validated prognostic markers (maximum high-sensitivity troponin (hs-Tn), C reactive protein (CRP) levels at admission, Synergy between percutaneous coronary intervention with Taxus and Cardiac Surgery (SYNTAX) score).MethodsWe measured serum tryptase at admission in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…Issues related to specificity likely include the small increases in sAT concentrations occurring with random variations or nonanaphylactic events, and mechanisms of anaphylaxis that do not involve MC degranulation . Indeed, MC activation has been reported in atherosclerosis‐related cardiovascular events, coagulation abnormalities, and response to infectious agents . In line with previous cohorts, our results confirm that the consensus algorithm sAT >([1.2 × sBT] + 2) μg/L is a good compromise between empirical thresholds such as >(1.35 × sBT), which privileged sensitivity as high as 0.91 in previous literature and 0.81 in our study, or (sBT + 3) μg/L, which resulted in sensitivity values as low as 0.63 in the literature and 0.72 in our hands.…”
Section: Discussionsupporting
confidence: 84%
“…Issues related to specificity likely include the small increases in sAT concentrations occurring with random variations or nonanaphylactic events, and mechanisms of anaphylaxis that do not involve MC degranulation . Indeed, MC activation has been reported in atherosclerosis‐related cardiovascular events, coagulation abnormalities, and response to infectious agents . In line with previous cohorts, our results confirm that the consensus algorithm sAT >([1.2 × sBT] + 2) μg/L is a good compromise between empirical thresholds such as >(1.35 × sBT), which privileged sensitivity as high as 0.91 in previous literature and 0.81 in our study, or (sBT + 3) μg/L, which resulted in sensitivity values as low as 0.63 in the literature and 0.72 in our hands.…”
Section: Discussionsupporting
confidence: 84%
“…In patients who had an ST segment elevation myocardial infarction, post percutaneous intervention tryptase negatively correlated with myocardial reperfusion and left ventricular ejection fraction [61]. Hence, patients who experienced major adverse cardiovascular events 2 years post ACS had higher baseline and discharged tryptase levels than those who did not [62,63]. This finding was independent of troponin and C-reactive protein levels [63].…”
Section: Cardiovascular Diseasementioning
confidence: 92%
“…Spikes in tryptase titers can be considered a marker of anaphylaxis [1,2], whereas increments in basal serum tryptase (BST) levels can be considered a marker of increased mast cell burden, as in mastocytosis [3], or of circumscribed inflammation, as in coronary atherosclerosis. In the follow-up of patients with previous acute coronary syndrome (ACS), we found that persisting elevated BST levels correlated with an increased risk of major adverse cardiovascular events (MACE) [4,5]. In other cases, high BST levels were shown to be biomarkers for the risk of severe allergic reactions to hymenoptera venom [6].…”
mentioning
confidence: 99%
“…One population comprised patients with hymenoptera venom allergy (HVA) and a history of Mueller grade III and IV anaphylactic reactions [7]. The second population comprised patients with a history of ACS that we had previously described in 2 studies and now includes 9 new patients [8,5]. The statistical evaluation was based on a descriptive analysis, followed by inference using the Fisher exact test for categorical variables.…”
mentioning
confidence: 99%
See 1 more Smart Citation